Investigation of work function and chemical composition of thin films of borides and nitrides. (17th April 2018) - Mezzi, A.; Soltani, P.; Kaciulis, S.; Bellucci, A.; Girolami, M.; Mastellone, M.; Trucchi, D. M.
Abstract : Thin films of various borides, nitrides, and barium fluorides were tentatively deposited by pulsed laser deposition and by magnetron sputtering in order to develop the components of thermionic‐photovoltaic devices for the high‐temperature thermal to electrical conversion by solid state. To improve the device performance, the materials characterized by a low work function were selected. In the present work, the chemical composition and work function of obtained films were investigated by X‐ray photoelectron spectroscopy and ultraviolet photoelectron spectroscopy techniques. The values of work function were determined from the cut‐off in the He I valence band spectra. Different films were compared and estimated on the basis of X‐ray photoelectron spectroscopy and ultraviolet photoelectron spectroscopy results.